Healthcare choices, information and health outcomes - Achyuta Adhvaryu; Anant Nyshadham (Yale University, Economic Growth Center, 2011)
Self-selection into healthcare options biases estimates of the effects of healthcare on health outcomes. We exploit exogenous variation in the cost of formal-sector care to show that the use of such care improves short-term health outcomes for acutely ill children in Tanzania. Better treatment-specific information, rather than greater access to medicines, appears to be the primary mechanism for this effect: children who use formal-sector care are as a result more likely to get timely treatment and adhere to their medications.
Keywords: I10; I18; O10; O12; 330; healthcare; information; child health; Tanzania